2019
DOI: 10.1590/1980-0037.2019v21e59839
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of combined training on the performance of the Brazilian women’s basketball team

Abstract: Competitions are considered of paramount importance for high-performancesports because they determine the entire orientation of the training process. When analyzing the calendar of the International Basketball Federation, it can be observed that international competitions occur in short periods of time. In this sense, the aim of this study was to verify the effects of the application of combined training in the short-term preparation period on the speed of athletes of the Brazilian women’s basketball team. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…More specifically, vertical jumping ability was significantly improved after 3 (8.08%), 8 (~8.77%) and 10 weeks (7-12.2%) of preseason plyometric and block periodization training in female and male elite basketball athletes [30][31][32]. Sprint performance was also significantly improved after 3 (1.55%), 4 (1.49%) and 6 (~1.25-1.65%) weeks of preseason training in female and male elite basketball athletes, through 10 and 20 m sprinting tests [30,31,33]. Some other studies demonstrated a significant effect of plyometric training on explosiveness through 5 m sprinting tests on young basketball players (~4%) [12,34].…”
Section: Discussionmentioning
confidence: 96%
“…More specifically, vertical jumping ability was significantly improved after 3 (8.08%), 8 (~8.77%) and 10 weeks (7-12.2%) of preseason plyometric and block periodization training in female and male elite basketball athletes [30][31][32]. Sprint performance was also significantly improved after 3 (1.55%), 4 (1.49%) and 6 (~1.25-1.65%) weeks of preseason training in female and male elite basketball athletes, through 10 and 20 m sprinting tests [30,31,33]. Some other studies demonstrated a significant effect of plyometric training on explosiveness through 5 m sprinting tests on young basketball players (~4%) [12,34].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the study of Borin et al, 2019 [32] demonstrated a significant decrease in agility after a typical pre-season training protocol (−2.3%). Finally, a possible explanation for the three studies that showed a significant decrease or did not return any significant outcomes in agility [15,30,32], might be the short duration of the pre-season period that was used (6, 4, and 4 weeks, respectively), compared to the other three studies that used longer pre-season training protocols (8, 8, and 12 weeks) (Table 3).…”
Section: Effects Of Pre-season Training On Balance Postural Control A...mentioning
confidence: 99%
“…The only study that evidenced significant improvements in speed ability (1.42 s) used a plyometric training program [26]. Additionally, in two other studies, a four-week pre-season training program was used, but the results suggest that a short-term training protocol was not efficient to improve the speed of female basketball athletes [17,32]; compared to the study of Asadi et al, 2017, [26] which used a different training modality and a longer training period of eight weeks. In two further studies [28,33] with the same RSA training protocol, the researchers tried to evaluate RSA, also comparing it with a typical pre-season training protocol [28], and found that the groups that were practicing with repeated sprint training during the pre-season period, showed a significant increase in RSA (0.2 s).…”
Section: Effects Of Pre-season Training On Speed and Repeated Sprint ...mentioning
confidence: 99%